Analysis of The Effect of Decentralization and The Effectiveness of Management Accounting Information Systems on Managerial Performancen - Ayke Nuraliati; Risma Nurani (JASa (Jurnal Akuntansi, Audit dan Sistem Informasi Akuntansi), 2022)
The technological revolution has hit all aspects of human life. In the business world in particular, the technological revolution has caused tremendous changes in competition, marketing and human resource management. With globalization, very large companies cannot be controlled and managed by one person so that the performance of these companies is not as good as decentralized companies. Where companies need to make decisions quickly and accurately, so that with good decentralization it will improve the performance of managers. Companies also need an effective management accounting information system to produce quality information so that it will improve managerial performance This study was conducted to determine the effect of decentralization and the effectiveness of management accounting information systems on managerial performance at PT. Main Greentextile Indonesia II Bandung. This research is a quantitative descriptive research by distributing questionnaires to collect the required data. The population of this study were middle and lower managers with a sample of 33 managers at PT. Main Greentextile Indonesia II Bandung. This study uses data analysis techniques used are descriptive statistics, multiple linear regression techniques. The results of this study indicate that 1) Decentralization has an effect on managerial performance at PT. Main Greentextile Indonesia II Bandung. 2) The effectiveness of the management accounting information system consisting of broad scope, timelines, aggregation, and integration has no effect on managerial performance at PT. Main Greentextile Indonesia II Bandung.